Mango Seed Kernel Extract as a Natural Antioxidant in Minced Fish During Frozen Storage - Praphan Pinsirodom; Chaianun Namngam; Ruchira Taprap; Sitthipong Nalinanon; Katherine Gabrielle Thompson; Yuporn Puechkamutr (My University, 2021)
Mango seed kernel extract (MSKE) has been reported to contain high content of phenolic compounds, and exhibit strong in vitro antioxidant activity. This study aimed to evaluate the application of MSKE as natural antioxidant in frozen minced fish products. The effect of MSKE at different concentrations (0%, 1%, 2% and 3% w/w) on retarding lipid and protein oxidation in minced fish samples during frozen storage at -18 ºC was investigated and compared to the chemical antioxidant, BHT (butylated hydroxytoluene) at 0.01% w/w. Physicochemical parameters related to the oxidative stability of minced fish samples including pH, color, peroxide value (PV), thiobarbituric acid reactive substances (TBARS), conjugated diene (CD), protein carbonyl, sulfphydryl groups (SH), and total volatile base nitrogen (TVB-N) were determined. The results showed that the pH values had significantly increased in all samples being treated with MSKE and BHT after 12 weeks of frozen storage. Samples treated with 3% MSKE or BHT were significantly lower in lightness (L*) and redness (a*) but presented no significant effects on yellowness (b*). Moreover, MSKE at all concentrations studied, and BHT, significantly delayed the increase in values of PV, TBARS, CD, protein carbonyl, and TVB-N and the decrease in values of SH compared to the control sample. At the end of storage, no significant odd odor and flavor assessed by sensory test were detected in frozen minced fish. In conclusion, MSKE at 3% w/w proved to be as efficient as BHT in retarding lipid and protein oxidation in minced fish during frozen storage.
Keywords: TBARS; Butylated hydroxytoluene; Lipid Oxidation; Thiobarbituric acid; Peroxide value; Palm kernel; Meat and Animal Product Quality